The leucine-responsive regulatory protein, Lrp, modulates microcin J25 intrinsic resistance in Escherichia coli by regulating expression of the YojI microcin exporter - Socias, Sergio Benjamin (2009)
Many Escherichia coli K-12 strains display an intrinsic resistance to the peptide antibiotic microcin J25. In this study, we present results showing that the leucine-responsive regulatory protein, Lrp, is involved in this phenotype by acting as a positive regulator of YojI, a chromosomally encoded efflux pump which expels microcin out of cells. Exogenous leucine antagonizes the effect of Lrp, leading to a diminished expression of the pump and an increased susceptibility to microcin J25. © 2009, American Society for Microbiology. All Rights Reserved.